Praktik Khalwāt dan Spiritualitas: Pengalaman Religius Santri di Pondok Pesantren - Defa Fatma Sari; Zainul Abas (LaKaspia, 2025)
Objective: This study aims to explore the meanings and dynamics of the religious experiences of students undertaking khalwāt at Al-Hikmah Islamic Boarding School in Gatak, Sukoharjo. Method: A qualitative approach with a phenomenological design was employed. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using Interpretative Phenomenological Analysis (IPA). Data validity was ensured through method and source triangulation. Results: Khalwāt is perceived not merely as a spiritual ritual but as a process of constructing personal and transformative religious meaning. Participants reported significant changes across affective, cognitive, and spiritual dimensions, including increased inner tranquility, greater discipline in religious practice, and deeper self-awareness. They also experienced mystical phenomena, interpreted as part of spiritual testing and purification. Conclusion: Khalwāt functions as a strategic inner spiritual space that strengthens spirituality and fosters the sustained development of students’ religious subjectivity.